Pertanggung Jawaban Pidana Karyawan Korporasi Dalam Tindak Pidana Lingkungan Hidup (Studi Putusan No. 133/Pid.B/2013/PN. MBO) - Andika Try Anantama; Zaini Munawir; Rafiqi Rafiqi (Universitas Medan Area, 2020)
Environmental Crimes committed by a person or corporate legal entity often occur around the environment where we live without us knowing it, especially in an environment full of companies that can damage the surrounding environment. The research method used in this study is juridical normative and descriptive analytical nature of the study. The legal regulation on environmental crime, especially regarding forest and land burning is regulated in Article 187 of the Criminal Code, Article 78 paragraph (3) of Law Number 41 of 1999 concerning Forestry, Article 69, Article 108 and Article 119 of Law Number 32 of 2009 Regarding Environmental Protection and Management, Article 48 of Law Number 18 Year 2004 Plantations. Criminal liability of corporate offenders in imprisonment for 3 (three) years and a fine of Rp. 3,000,000,000 (three billion rupiah), Determine if the fine is not paid replaced with imprisonment for 5 (five) months. Judge's consideration in this decision, that the Defendant violated Article 108 in conjunction with Article 69 paragraph (1) letter (h) jo Article 116 paragraph (1) letter (b) of Law Number 32 of 2009 concerning Environmental Protection and Management and jo Article 64 paragraph (1) of the Criminal Code has several considerations, namely incriminating circumstances and mitigating circumstances.